2007
DOI: 10.1007/s11655-007-0156-z
|View full text |Cite
|
Sign up to set email alerts
|

Progress in research on applying Sijunzi Decoction (四君子汤) in treating digestive malignant tumor

Abstract: Patients with digestive malignant tumor always have their immune function, especially the cellular immunity, suppressed to a certain extent. Traditional Chinese medicine (TCM) holds that Pi-Wei is the essence of postnatal life, and the genesis and development of digestive tumor are chiefly due to the insufficiency of vital-qi, which makes the body open to the invasion of evil pathogens. Starting from regulating the immune function of organisms, researchers recently obtained some therapeutic effects by applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 2 publications
0
13
0
1
Order By: Relevance
“…According to clinical studies performed over the past few decades, SJZD has been used to treat patients with chronic gastritis or chronic atrophic gastritis, nausea, vomiting and diarrhoea (Liu, Yang, & Cai, ; Yu et al, ). Moreover, SJZD has been shown to control tumor progression, prolong patients’ lives, improve their quality of life (Guo & Zhang, ), prevent recurrence and metastasis in postoperative patients (Huang, Xi‐Hua, & Chen, ; Liang, Zhang, & Cai, ), and exert potential effects on immune system activation (Liu et al, ) and tumor therapy (Wu & Xuan, ).…”
Section: Introductionmentioning
confidence: 99%
“…According to clinical studies performed over the past few decades, SJZD has been used to treat patients with chronic gastritis or chronic atrophic gastritis, nausea, vomiting and diarrhoea (Liu, Yang, & Cai, ; Yu et al, ). Moreover, SJZD has been shown to control tumor progression, prolong patients’ lives, improve their quality of life (Guo & Zhang, ), prevent recurrence and metastasis in postoperative patients (Huang, Xi‐Hua, & Chen, ; Liang, Zhang, & Cai, ), and exert potential effects on immune system activation (Liu et al, ) and tumor therapy (Wu & Xuan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmacological studies show that this prescription affects several other physiological functions such as improving gastrointestinal function [5], strengthening the immune system [6, 7], improving bone marrow hematopoietic function, and speeding up the production of red blood cells. This prescription can also be used for the treatment of malignant tumors of the digestive tract [8]. Xiao and Yang found that Si-Jun-Zi Decoction could improve the immune function and quality of life and reduce the side effects of chemotherapy in patients with colorectal cancer undergoing chemotherapy [7].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, SJZD has been used to treat peptic or gastric ulcer and disorders of the spleen (11). A clinical study has shown that SJZD improves the postoperative survival of patients with gastric carcinoma (12). One study demonstrated that SJZD effectively inhibited the growth of tumors in nude mice bearing SGC-7901 xenografts (13).…”
Section: Introductionmentioning
confidence: 99%